2012
DOI: 10.1186/1472-6939-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Can physicians’ judgments of futility be accepted by patients?: A comparative survey of Japanese physicians and laypeople

Abstract: Back groundEmpirical surveys about medical futility are scarce relative to its theoretical assumptions. We aimed to evaluate the difference of attitudes between laypeople and physicians towards the issue.MethodsA questionnaire survey was designed. Japanese laypeople (via Internet) and physicians with various specialties (via paper-and-pencil questionnaire) were asked about whether they would provide potentially futile treatments for end-of-life patients in vignettes, important factors for judging a certain tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Doctors from a range of specialties nominated doctor-related, patient-related and hospital-related factors that contributed to futile treatment. This research confirms the reasons for futile treatment identified in other studies, such as patient or family request for treatment,6–11 13–16 19 24 25 clinician practices (including poor communication skills6 7 9 11 15 19 21 24–26 and failure to diagnose end of life),11 21 24 fears of legal consequences,6 8–10 13 15 16 19 20 and institutional fragmentation and specialisation 9–11 13–15 19 21 24. It also reveals deeper insights into these causes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Doctors from a range of specialties nominated doctor-related, patient-related and hospital-related factors that contributed to futile treatment. This research confirms the reasons for futile treatment identified in other studies, such as patient or family request for treatment,6–11 13–16 19 24 25 clinician practices (including poor communication skills6 7 9 11 15 19 21 24–26 and failure to diagnose end of life),11 21 24 fears of legal consequences,6 8–10 13 15 16 19 20 and institutional fragmentation and specialisation 9–11 13–15 19 21 24. It also reveals deeper insights into these causes.…”
Section: Discussionsupporting
confidence: 83%
“…To achieve this, we must first understand the complex reasons why such treatment is provided. The literature points to a range of drivers of futile treatment at the end of life, emphasising family and patient request,6–11 13–16 19 24 25 poor communication with patients and families,6 7 9 11 15 19 21 24–26 lack of knowledge about patient wishes,12 13 15 24 conflict with colleagues10 11 13–15 24 25 and legal concerns 6 8–10 13 15 16 19 20. Some also suggest that doctors are responsible for futile treatment (although to a lesser degree than patients or families)7 11 15 19 21 24 27 and a few point to institutional reasons such as time pressure 16 24…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that personal, religious, and cultural beliefs and values as well as socioeconomic factors can contribute to futility. 4,13,14,16,44,49,50 In most cases, health care professionals consider implementing lifesaving interventions for terminally ill patients as futile while patients' families believe that such interventions are effective at least in helping them effectively cope with losing a family member. 7, 46 Whitmer et al 16 also noted that medical futility is a subjective concept that is defined and perceived differently by different people.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, futility is a complex concept 4,7 because no consensus exists over its definition 4,14,17,18,49 and different factors affect people's perceptions of it. 4,8,9,16,44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation